Penerapan Book & Quiz dan Google Classroom Sebagai Media Pembelajaran di Masa Pandemi COVID-19 - Winda Monika; Arbi Haza Nasution; M. Rizki Fadhilah; Hafiza Oktasia Nasution (Universitas Lancang Kuning, 2022)
The COVID-19 pandemic presents its own challenges in the education sector (schools) to adapt quickly so that they can still carry out and present education optimally to students even in limited circumstances. One of the efforts that continue to be made by the school is the application of information technology as a learning medium. The partner for this Community Service activity is SMP YLPI Marpoyan Pekanbaru, which during the pandemic experienced obstacles in using the library and using the Learning Management System (Google Classroom). To that end, the team built the book&quiz application and conducted training on the use of the book&quiz application and Google Classroom. The application of the book&quiz application is believed to be able to facilitate the management of digital libraries and increase students' reading interest. In addition, the use of Google Classroom can support more optimal online class management. Overall, the teachers are very satisfied and helped by this community service activity.